Mitral valve surgery after failed transcatheter edge-to-edge repair: a review and word of caution. (28th March 2023) - El-Eshmawi, Ahmed; Costa, Ana Claudia; Boateng, Percy; Pandis, Dimosthenis; Israel, Yonatan; Adams, David H.; Tang, Gilbert H.L.
Abstract : Purpose of review: As transcatheter edge-to-edge mitral valve repair (TEER) evolves and indications broaden to include younger and lower surgical risk patients, it is essential to understand TEER failure trends and potential impact on subsequent mitral valve surgery, especially when pertaining to feasibility of durable valve reconstruction as opposed to de-novo repair. Recent findings: Results of the two largest series analysing mitral valve surgery following TEER have demonstrated remarkably low repairability rates with consequent need for valve replacement. Post TEER surgery was associated with high early and late mortalities, likely as a reflection of patient baseline characteristics and acuity of surgery. Presence and correction of concomitant cardiac pathologies were a frequent finding. Centre and surgeon volumes were important factors in optimizing the likelihood of salvage repair and reducing perioperative risks. Summary: Surgical mitral valve repair in reference centres remain the gold standard and the most durable treatment for degenerative mitral disease with excellent perioperative safety outcomes. Given the high likelihood of needing high-risk mitral valve replacement when TEER fails, consideration for potentially less durable transcatheter alternatives should be taken with caution in younger or lower surgical risk patients.